Effects of the New York State Workers Compensation Board Medical Treatment Guidelines on Return to Work. Issue 7 (July 2018) - Demian, Cristina; Barron, Bruce; Almudevar, Anthony
Abstract : Objective: Examine the association between New York State Workers' Compensation Medical Treatment Guidelines (Guidelines) adherence and return-to-work after occupational low back injuries. Assess adherence to Guidelines by examining diagnostic and treatment utilization. Method: Retrospective chart review of cases. Outcomes of interest were lost time duration and diagnostic/treatment utilization rates. Time to event analyses performed using Kaplan–Meier plots and Cox proportional hazard model. Results: Care received after implementation of Guidelines resulted in decreased lost time. Treatment rates were consistent, while diagnostic imaging use was inconsistent with Guidelines recommendations. Conclusions: Guidelines use positively influenced return-to-work after acute occupational low back injuries. Inconsistencies in following Guidelines were observed for diagnostic tests, having a potential paradoxical effect on lost time. Further studies are necessary to test for additional hypotheses. Abstract : Supplemental Digital Content is available in the text